Striae distensae in adolescents: A mini review - Elsedfy, Heba (Acta Biomedica Atenei Parmensis, 2020)
Striae distensae or stretch marks are mainly a cosmetic concern. They commonly occur in adolescence and in pregnant women. Although, generally more common in females; physiological striae atrophicae of adolescence are more common in males. The pathophysiology is multifactorial with mechanical stretching of the skin being the most important. Despite of an abundance of treatment modalities none is 100% effective.